Encyclopedia of Inorganic and Bioinorganic Chemistry 2014
DOI: 10.1002/9781119951438.eibc2206
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks: Porphyrinic Frameworks

Abstract: There has been growing interest in coordination chemistry, particularly in the field of porous metal–organic frameworks (MOFs). Since the functionalities of MOFs can be systematically tuned by integrating functional groups in their frameworks, MOF materials have been realized applications in a number of fields, including luminescence, gas storage, sensing, magnetics, and catalysis. Because porphyrins and metalloporphyrins have rigid structures and remarkable functionalities of catalysis, charge, and energy tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…[42] Replacing the labile NDIDB 2− ligand in BUT-109(Zr) to a robust one may strengthen the framework structure and deliver a new functional MOF. Given the structural rigidity and multifunctional feature of porphyrins, as well as the matching molecular size and geometry with NDIDB 2− , a di-carboxylic acid porphyrin ligand 4,4'-(porphyrin-5,15-diyl) dibenzoic acid (H 2 DCPP) [43] (Figure S1, Supporting Information) was selected as the competing ligand to substitute NDIDB 2− in BUT-109(Zr) (Figure 1a). Subsequently, the H 2 DCPP substitution reaction for a stable and versatile MOF was conducted by modifying BUT-109(Zr) in different ways (Figures 1b and 2).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] Replacing the labile NDIDB 2− ligand in BUT-109(Zr) to a robust one may strengthen the framework structure and deliver a new functional MOF. Given the structural rigidity and multifunctional feature of porphyrins, as well as the matching molecular size and geometry with NDIDB 2− , a di-carboxylic acid porphyrin ligand 4,4'-(porphyrin-5,15-diyl) dibenzoic acid (H 2 DCPP) [43] (Figure S1, Supporting Information) was selected as the competing ligand to substitute NDIDB 2− in BUT-109(Zr) (Figure 1a). Subsequently, the H 2 DCPP substitution reaction for a stable and versatile MOF was conducted by modifying BUT-109(Zr) in different ways (Figures 1b and 2).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[53] Porphyrin shows excellent lightharvesting ability, and the ordered structure of porphyrin-based MOFs can distribute these units uniformly in space, further improving their catalytic efficiency. [43,[54][55][56][57][58][59] Hence, porphyrin-MOFs represents a promising class of heterogenous photocatalysts. Jiang and co-workers have demonstrated that PCN-222 can selectively capture and convert CO 2 to HCOO − anion with high efficiency under visible-light irradiation.…”
Section: Photocatalytic Co 2 Reductionmentioning
confidence: 99%